Battle Against Musculoskeletal Tumors: Descriptive Data of Military Hospital Experience - Cagri Neyisci; Yusuf Erdem (Frontiers Media S.A., 2020)
Background: Management of musculoskeletal tumors remains challenging for orthopedic surgeons. The aim of this cross-sectional study was to present the prevalence and localization of musculoskeletal disorders diagnosed and treated at a tertiary referral military hospital.Method: A total of 552 patients' medical records who presented to our clinic between 2009 and 2014 with the diagnosis of musculoskeletal tumors were retrospectively analyzed according to age, gender, bone/soft tissue localization, histopathological diagnosis, incidence, and treatment.Results: Of the cases diagnosed with tumor, 225 were soft tissue localized, 317 bone localized, and 10 tumor-like lesions. The most common primary benign soft tissue tumors were lipoma, ganglion, and giant cell tumor of tendon sheath, while the most common malignant soft tissue tumors were liposarcoma and synovial sarcoma, respectively. The most common primary bone tumors were osteochondroma, enchondroma, and simple bone cyst, while the most common malignant bone tumors were osteosarcoma, Ewing sarcoma and chondrosarcoma, respectively. Myositis ossificans was found as the most common tumor-like lesion.Conclusion: Descriptive data in musculoskeletal tumors is crucial in terms of improving treatment and reducing mortality. In this study, no significant difference was found between the data of tertiary military hospital regarding epidemiology of musculoskeletal system tumors and those from the literatures around Turkey.